Antibacterial effect of ethanolic extract of centella Asiatica and cosmos caudatus on escherichia coli - Amirah Husna Abdul Halim (2022)
Antibacterial activity of Centalla asiatica (pegaga) and Cosmos caudatus (ulam raja) extract was carried out against Escherichia coli. The aim of this study is to determine antibacterial effects of ethanolic extract of C. asiatica and C. caudatus against E. coli at different concentrations. By using a rotary vacuum evaporator, Ethanol was used to prepare C. asiatica and C. caudatus. Ethanolic extract C. asiatica and C. caudatus was prepared and divided into five concentration which are 6250μg/mL, 12500μg/mL, 25000g/mL, 50000μg/mL, and 100000μg/mL. The findings of this study revealed that E. coli is highly resistant to C. asiatica and C. caudatus thus, not making them appropriate antibacterial agents for E. coli infection. Keywords: antibacterial activity, Centella asiatica, Cosmos caudatus